Estudios del trabajo desde el sur. Vol. V - Bravo Armazabal, Luz; Julián-Vejar, Dasten; Galliorio Jorquera, Álvaro (Ariadna Ediciones, 2023)
This new volume of Labor Studies from the South is forged in a hectic contingency. And it is that since April 2022 (date on which the previous volume was published) a series of events occurred that marked the process of its elaboration, among them, the vote of the plebiscite ofoutput of the constitutional proposal elaborated by the elected convention, the first year of Gab's management